Potensi Penerimaan Pajak Galian Golongan C Dikabupaten Melawi Tahun 2020-2022 - Oktavia, Maylanda Fitri; Kumala, Ratih (Jurnal Ilmu Administrasi Publik, 2024)
Tax plays a vital role in supporting national income. Taxes can be utilized for developmental purposes to support the governance of their respective regional administrations; wherein local governments are entitled to levy Local Taxes and Regional Levies on all Taxpayers within their jurisdictions. This study aims to identify and analyze the Potential Tax Revenue of Category C Excavation Tax in Melawi District for the years 2020-2022. It also aims to identify the obstacles faced and efforts made to overcome these obstacles in realizing the potential revenue from Category C excavation tax. This research utilizes a qualitative descriptive research method. The research is conducted at the Melawi District Revenue Agency Office. Data collection is carried out through observation, interviews, and documentation. The results of the study show that the Potential Tax Revenue of Category C Excavation Tax in Melawi District for the years 2020-2022 has been reasonably good, but the potential excavation remains underutilized. In 2020, the revenue realization was 21.19%, amounting to IDR 1,208,104,004. In 2021, it was 43.36%, amounting to IDR 2,916,126,980, and in 2022, it was 43.11%, amounting to IDR 3,004,415,661. The potential tax revenue over the past 3 years has been underutilized due to a lack of taxpayer awareness in reporting their taxes. To address these obstacles, efforts can be made by providing public awareness campaigns, enhancing the knowledge and skills of human resources through training, technical guidance, and other means.